Quality of life of a healthy polish population due to sociodemographic factors during the COVID-19 pandemic – a cross-sectional study - Krawczyk-Suszek, Marlena; Kleinrok, Andrzej (Frontiers in Public Health, 2023)
Introduction The quality of life should be studied in every person, both among the sick and healthy. Sociodemographic factors affect the level of the perceived quality of life (QoL), and especially in the situation of the COVID-19 pandemic, which forced the enforcement of certain behaviours in society, such as social distancing, as well as introduced panic and fear for one’s own health and life. The main aim of the study was to assess the quality of life in the group of people without the disease, to assess the impact of sociodemographic factors on QoL during the pandemic. Material and method 3,511 healthy people were included in the study. The inclusion criteria of the study were: age of respondents over 18 years, no continuously administered medicaments, no diagnosed chronic diseases and no treatment in specialist clinics as well as lack of positive COVID-19 test in 4 weeks before the examination. The SF-36 questionnaire was used to assess the quality of life. The student’s t-test and intergroup comparisons were used in 7 age groups. Factors such as age, gender, place of residence, education, civil status, employment status, smoking, and physical activity were assessed. Results The lowest average QoL level in the studied population was recorded in the Mental Component Summary (MCS) dimension (X = 47.9;Cl:47.6–48.3). A high correlation between age and the SF-36 spheres was noted in the following spheres: physical functioning (PF), role physical (RP), Physical Component Summary (PCS), and ILQ (p < 0.001). The highest chance of a better QoL in the PCS dimension among men was recorded in the 30–39 age group (OR = 3.65;Cl:1.13–11.79). In the group of people over 50 years of age living in the village, there was a greater chance of a better QoL in the PCS dimension in each age group. Practicing physical activity was significantly more often conditioned by a higher chance of developing a better QoL (p < 0.05). In the group of people ≥80 years of age, there was a greater than 4 times higher chance of developing a better quality of life in terms of MCS among physically active people (OR = 4.38;Cl:1.62–11.83). Conclusion With age, QoL decreases among people with disabilities. Men are more likely to assess their health better. A better QoL among women occurs at age 80 and later. A higher level of education often determined a significantly higher level of QoL felt. The practising of recreational physical activity and the lack of smoking habit determined a higher level of QoL more often. Smoking provided a greater chance of a better QoL in ILQ in the group of people ≥80 years.